The Value of Tolerance Education in the Qur'an Surah Az-Zumar Verse 18 - Mohammad Al-Farabi; Yusnaili Budianti; Sahirman Ahmad Batubara (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
This study aims to find, describe, and analyze in depth the meaning of the interpretation contained in Surah az-Zumar verse 18 along with the educational values â€‹â€‹of tolerance that can be learned in its content. This thesis study also seeks to find the relevance of the educational values â€‹â€‹of tolerance with the concept of contemporary Islamic education. This study uses a qualitative method with descriptive analysis of the data obtained through library research. The collected data is processed by content analysis techniques, which are integrated with tahlili analysis techniques sourced from the Qur'an and Hadith as well as 21 classical and contemporary tafsr books as primary data, and supported by secondary data sources originating from various sources. literature, such as muÊ»jam (dictionary), and supporting books related to the field of study being researched. The results of the research in this thesis found that: (1) The meaning contained in surah az-Zumar verse 18 contains the basics of tolerance education which contains learning about the ethics of listening to conversations, respecting, and respecting messages conveyed by Allah SWT. and Rasulullah saw., as well as from fellow human beings, then take the values â€‹â€‹of goodness and practice these messages in everyday life called Å«lul albÄb; (2) The values â€‹â€‹of tolerance education found in Surah az-Zumar verse 18 contain several aspects, namely a strong aqidah full of obedience, appreciation, respect, patience, smart thinking, forgiveness, independence, controlling lust and delusions, adab and morals, courage, peace, standing firm (istiqÄmah), advice, rights and obligations, love, unselfishness, and justice. These values â€‹â€‹of tolerance education have strong relevance to the implementation of the concepts of Contemporary Islamic Education being developed today, including character education, multicultural education, environment-based learning, cooperative learning, and quantum learning. Keywords:Value, Tolerence, Education.